197k views
3 votes
If f(x)=x-3/x, g(x)=x+3, and h(x)=2x+1, what is (g o h o f)(x)?

User Tjltjl
by
5.1k points

2 Answers

0 votes

So, (g o h o f)(x) = g((hof)(x));

But, (hof)(x) = h(f(x)) = 2·f(x) + 1 = 2·( x - 3/x) + 1 = 2x - 6/x + 1;

Then, g(2x - 6/x + 1) = 2x - 6/x + 1 + 3 = 2x -6/x + 4.

User Arno Hilke
by
5.7k points
3 votes

Answer:


(gohof)(x)=2x-(6)/(x)+4

Explanation:

We need to find out
(gohof)(x)

Given:-
f(x)=x-(3)/(x), \ g(x)=x+3 \ \text{and} \ h(x)=2x+1

First we calculate
(hof)(x)


(hof)(x)=h(f(x))


(hof)(x)=2x+1


(hof)(x)=2(x-(3)/(x))+1


(hof)(x)=2x-(6)/(x)+1

Now,Put (hof)(x) in g(x)


(gohof)(x)=g(h(f(x)))


(gohof)(x)=g((hof)(x))


(gohof)(x)=2x-(6)/(x)+1+3


(gohof)(x)=2x-(6)/(x)+4

Therefore,
(gohof)(x)=2x-(6)/(x)+4

User Tyler B
by
6.0k points